Natural History and Predictors of Progression to Sjögren's Syndrome Among Participants of the Sjögren's International Collaborative Clinical Alliance Registry. Issue 2 (3rd January 2018) - Shiboski, Caroline H.; Baer, Alan N.; Shiboski, Stephen C.; Lam, Mi; Challacombe, Stephen; Lanfranchi, Hector E.; Schiødt, Morten; Shirlaw, Penelope; Srinivasan, Muthiah; Umehara, Hisanori; Vivino, Frederick B.; Akpek, Esen; et al.
Abstract : Objective: To explore changes in the phenotypic features of Sjögren's syndrome (SS), and in SS status among participants in the Sjögren's International Collaborative Clinical Alliance (SICCA) registry over a 2–3‐year interval. Methods: All participants in the SICCA registry who were found to have any objective measures of salivary hypofunction, dry eye, focal lymphocytic sialadenitis in minor salivary gland biopsy, or anti‐SSA/SSB antibodies were recalled over a window of 2 to 3 years after their baseline examinations to repeat all clinical examinations and specimen collections to determine whether there was any change in phenotypic features and in SS status. Results: As of September 15, 2013, a total of 3, 514 participants had enrolled in SICCA, and among 3, 310 eligible, 771 presented for a followup visit. Among participants found to have SS using the 2012 American College of Rheumatology (ACR) classification criteria, 93% again met the criteria after 2 to 3 years, and this proportion was 89% when using the 2016 ACR/European League Against Rheumatism (EULAR) criteria. Among those who did not meet ACR or ACR/EULAR criteria at baseline, 9% and 8%, respectively, had progressed and met them at followup. Those with hypergammaglobulinemia and hypocomplementemia at study entry were, respectively, 4 and 6 times more likely to progress to SS by ACR criteria than those without these characteristics (95% confidence interval 1.5–10.1 and 1.8–20.4, respectively). Conclusion: While there was stability over a 2–3‐year period of both individual phenotypic features of SS and of SS status, hypergammaglobulinemia and hypocomplementemia at study entry were predictive of progression to SS.